2006
DOI: 10.1108/01437730610677990
|View full text |Cite
|
Sign up to set email alerts
|

Causal inferences between participation in decision making, task attributes, work effort, rewards, job satisfaction and commitment

Abstract: PurposeRegulatory frameworks in Australia encourage employee participation in decision making (PDM) on the basis that participation benefits work effort, job satisfaction and commitment. Although the literature supports this premise, there is little evidence that patterns of causal inference in the relationship are clearly understood. This study aims to examine for structural and causal inference between PDM and the work environment over time.Design/methodology/approachStructural equation modeling was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
105
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 46 publications
17
105
0
8
Order By: Relevance
“…These results were consistent with findings from existing empirical literature (Black & Gregersen, 1997;Schuler, 1980;Scott-Ladd et al, 2006), which have suggested that when employees can engage in higher levels of PDM, their job satisfaction would also be likely to increase. From a theoretical perspective, encouraging PDM is provided under the affective models of participation, whereby facilitating employee engagement in job-related decisions will lead to the attainment of their higher-order needs (Maslow, 1943), which will ultimately promote their job satisfaction (Vroom, 1964).…”
Section: The Relationship Between Job Satisfaction and Participativesupporting
confidence: 82%
“…These results were consistent with findings from existing empirical literature (Black & Gregersen, 1997;Schuler, 1980;Scott-Ladd et al, 2006), which have suggested that when employees can engage in higher levels of PDM, their job satisfaction would also be likely to increase. From a theoretical perspective, encouraging PDM is provided under the affective models of participation, whereby facilitating employee engagement in job-related decisions will lead to the attainment of their higher-order needs (Maslow, 1943), which will ultimately promote their job satisfaction (Vroom, 1964).…”
Section: The Relationship Between Job Satisfaction and Participativesupporting
confidence: 82%
“…Participation viewed this way might be related to functional diversity as well, as participation would allow various diverse viewpoints to benefit the work group as a whole. This is consistent with other considerations of participation in decision-making within organizations, such as Scott-Ladd, Travaglione, and Marshall (2006), who note an indirect positive relationship between participation and performance through increased affective commitment, job satisfaction, and performance effort.…”
Section: Work Group Inputssupporting
confidence: 73%
“…Para evaluar la autoeficacia de los profesores se utilizó el instrumento de- & Daytner, 1999). A pesar de que un análisis factorial reveló tres factores, estos estaban fuertemente correlacionados y conceptualmente relacionados, y por lo tanto elegimos tratarlos como uno solo que explicaba el 59.0% de la variación.…”
Section: Instrumentosunclassified